Strategi Komunikasi Inovasi UMKM dalam Pengembangan Keripik Sambal Pepaya sebagai Produk Pangan Lokal Berdaya Saing - Mailin Mailin; Azli Azumar Nasution; Mhd. Adjie Permana; Intan Fahzirah; Ahmad Habibi Daulay; Raihan Hidan Bugis; Mhd. Rivaldhy Harahap (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Local food innovation is not only focused on product development but also requires effective communication strategies to build positive perceptions and enhance market competitiveness. This study aims to analyze the implementation of innovation communication strategies by micro, small, and medium enterprises (MSMEs) in developing papaya-based chili chips as a flagship product in Nagori Karang Anyar, Gunung Maligas District, Simalungun Regency. The research employs a descriptive qualitative approach, focusing on the product innovation process, marketing communication patterns, and efforts to build product image amid competition in the local food industry. The findings indicate that innovation communication strategies play a crucial role in creating product differentiation through narratives of unique taste, utilization of local raw materials, and promotional strategies combining traditional methods and digital media. Papaya chili chips are positioned as a product that blends distinctive local flavors with a modern touch, attracting consumer interest and increasing the added value of papaya as a local commodity. This study emphasizes that the success of local food innovation depends not only on product quality but also on the ability of MSMEs to manage adaptive and persuasive communication strategies.